2018
DOI: 10.1111/luts.12245
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic magnetic resonance imaging parameters predict urinary incontinence after robot‐assisted radical prostatectomy

Abstract: Objective: Urinary incontinence (UI) is a major prostate cancer (PCa) treatment-related morbidity. It has been reported that post-prostatectomy UI is related to the width of the pelvic floor muscles (PFM) and the length of the urethra. However, the details of these anatomical parameters are unknown. The aim of this study was to investigate whether preoperative pelvic parameters or anatomical parameters of the urethra, as measured by magnetic resonance imaging (MRI), are correlated with UI. Methods: Between 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 21 publications
(30 reference statements)
4
46
0
1
Order By: Relevance
“…As they have been reported, many static cystographic findings could estimate the postoperative urinary continence. In addition to that, some researchers the similar results were reported using preoperative magnetic resonance imaging [10,11]. However, we believed that dynamic evaluation of cystography is needed.…”
Section: Discussionsupporting
confidence: 54%
“…As they have been reported, many static cystographic findings could estimate the postoperative urinary continence. In addition to that, some researchers the similar results were reported using preoperative magnetic resonance imaging [10,11]. However, we believed that dynamic evaluation of cystography is needed.…”
Section: Discussionsupporting
confidence: 54%
“…Average MUL in continent patients was 15.9 (±2.6) mm in the article by Song et al, 13 16.1 (95% confidence interval [CI]: 13.9–18.9) in the study by Regis et al, 12 14.5 in the article by Schmid et al, 15 and 12.1 (95% CI: 9.7–14.9) in the article of Sadahira 14 . Conversely, average MUL in incontinent patients was lower, 13.9 (±2.9) mm in Song, 13 10 (95% CI: 8.7–12.1) in Regis, 12 9.3 in Schmidt, 15 and 10.3 (95% CI: 8.7–12.4) in Sadahira 14 …”
Section: Resultsmentioning
confidence: 98%
“…Of the preoperative patient characteristics, several meta‐analyses revealed that older age, obesity, and the presence of comorbidities and lower urinary tract symptoms influence postoperative UIN 2‐4 . Of the pelvic MRI parameters, a short membranous urethral length, urethral wall thickness, levator ani muscle, large prostate volume, and intravesical prostatic protrusion were identified as predictive of postoperative UIN 4,6,7,9,10 . However, these studies were limited by biases in interobserver measurements or MRI acquisition conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for UIN after RP in patients with PCa have been reported by several studies 2‐10 . Among them, patient age and obesity are common factors influencing UIN 2‐4 .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation